Report of the Committee on the Elimination of Discrimination against Women, Sixty-third Session - United Nations Department for General Assembly; Conference Management (United Nations, 2008)
Official records of the Report of the Committee on the Elimination of Discrimination against Women: Fortieth Session (14 January-1 February 2008), Forty-first Session (30 June-18 July 2008)